2015
DOI: 10.1242/jcs.169821
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the roles of human BUB1 in the spindle assembly checkpoint

Abstract: Mitotic chromosome segregation is initiated by the anaphase promoting complex/cyclosome (APC/C) and its co-activator CDC20 (forming APC/C CDC20 ). APC/C CDC20 is inhibited by the spindle assembly checkpoint (SAC) when chromosomes have not attached to spindle microtubules. Unattached kinetochores catalyze the formation of a diffusible APC/C CDC20 inhibitor that comprises BUBR1 (also known as BUB1B), BUB3, MAD2 (also known as MAD2L1) and a second molecule of CDC20. Recruitment of these proteins to the kinetochor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
93
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 44 publications
8
93
1
Order By: Relevance
“…Mad1-Mad2 first catalyzes MCC assembly at interphase nuclear pores [3], then migrates to kinetochores at nuclear envelope breakdown (NEBD) and resumes MCC assembly until bipolar spindle attachment is complete [1,2]. There is significant debate about the factor(s) involved in targeting Mad1-Mad2 to kinetochores in higher eukaryotes [4][5][6][7][8][9]. Through gene editing and livecell imaging, we found that the human Rod-Zw10-Zwilch (RZZ) complex is dispensable for cell viability and initial recruitment of Mad1-Mad2 to kinetochores at NEBD, but then becomes necessary to tether Mad1-Mad2 at kinetochores and sustain SAC arrest in cells challenged with spindle poisons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mad1-Mad2 first catalyzes MCC assembly at interphase nuclear pores [3], then migrates to kinetochores at nuclear envelope breakdown (NEBD) and resumes MCC assembly until bipolar spindle attachment is complete [1,2]. There is significant debate about the factor(s) involved in targeting Mad1-Mad2 to kinetochores in higher eukaryotes [4][5][6][7][8][9]. Through gene editing and livecell imaging, we found that the human Rod-Zw10-Zwilch (RZZ) complex is dispensable for cell viability and initial recruitment of Mad1-Mad2 to kinetochores at NEBD, but then becomes necessary to tether Mad1-Mad2 at kinetochores and sustain SAC arrest in cells challenged with spindle poisons.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies in mammalian cells differ as to (1) whether Bub1 recruits Mad1-Mad2 to kinetochores and (2) whether and how Bub1 contributes to SAC arrest [4-7, 9, 41]. Recently several groups reported that the SAC in human cells is refractory not only to Bub1 depletion [4,6] but also stable disruption of the BUB1 locus [9, 46] unless Mps1 is partially inhibited to sensitize the system [9, 47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ABBA motif in Bub1 is required for a functional checkpoint and recruits a pool of Cdc20 to kinetochores. 3,4 Potentially the proximity of Cdc20 to the Mad1-Mad2 complex, coordinated by Bub1, facilitates the binding of Mad2 to Cdc20 the ratelimiting step in MCC formation.…”
mentioning
confidence: 99%